2021
DOI: 10.3390/f12050637
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Forest Landcover Changes in Coastal Vietnam: A Case Study from 1973 to 2020 in Thanh Hoa and Nghe An Provinces

Abstract: Mangrove forests can ameliorate the impacts of typhoons and storms, but their extent is threatened by coastal development. The northern coast of Vietnam is especially vulnerable as typhoons frequently hit it during the monsoon season. However, temporal change information in mangrove cover distribution in this region is incomplete. Therefore, this study was undertaken to detect change in the spatial distribution of mangroves in Thanh Hoa and Nghe An provinces and identify reasons for the cover change. Landsat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 81 publications
0
20
0
1
Order By: Relevance
“…The remaining 1,158,000 ha includes mangroves, other bamboo species, small monocultures of other native species, and some mixed forests. At present, there is no national strategy to investigate the health of these forests even though tree mortality has been observed [102,103]. These planted forests in Vietnam have potential pests and diseases, some of which may become invasive and damage new production forests in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 1,158,000 ha includes mangroves, other bamboo species, small monocultures of other native species, and some mixed forests. At present, there is no national strategy to investigate the health of these forests even though tree mortality has been observed [102,103]. These planted forests in Vietnam have potential pests and diseases, some of which may become invasive and damage new production forests in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thanh Hoa Province in north-central Vietnam was chosen because afforestation trials had been established in 2015, and remote sensing imagery showed that many plantings had been unsuccessful [47]. Thanh Hoa city (20.0 • N, 105.5 • E) has a tropical climate with intermittent rainfall concentrated in the summer (1447 mm/year), and the average annual temperature is 27.3 • C. Preliminary health surveys were randomly conducted in mangroves in two geographical areas (Table 2) to assess canopy conditions in 2018.…”
Section: Study Area and Canopy Assessmentmentioning
confidence: 99%
“…Large gaps remain in the documentation of mangrove diseases for most parts of northern Vietnam. As the average rate of success of mangrove restoration in northern Vietnam is approximately 30% [47], understanding whether mangrove diseases are a contributing factor could help improve the management of mangroves in future projects. Therefore, this study was undertaken to document the extent and impact of disease problems on afforested mangroves in Thanh Hoa Province.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal forests are an important part of tropical biodiversity. They provide a lot of important services for our ecosystem, such as extreme weather protection, erosion prevention, environments for different species, and storage of blue carbon, which allow to mitigate climate change [1]. However, these forests are increasingly vulnerable to degradation as a result of climate change, sea-level rise or anthropogenic processes such as deforestation [2].…”
Section: Introductionmentioning
confidence: 99%